Influence of reinforcing fiber on the dry sliding wear behavior of hybrid fabric/benzoxazine composites. Issue 23 (December 2019) - Su, Meng; Liang, Lei; Ren, Fang; Yao, Weigang; Yu, Mingming; Ren, Musu; Sun, Jinliang
Hybrid polyimide (PI)-polytetrafluoroethylene (PTFE)/Nomex fabric composites and Nomex-PTFE/Nomex fabric composites were prepared with benzoxazine (BOZ) as the resin binder. The tribological properties and wear mechanisms of the two composites at different temperatures were investigated using a ball-on-disk wear tester. Before sliding wear tests, a thermo-aging test, thermogravimetric analysis and dynamic mechanical analysis of PI and Nomex fibers were performed to evaluate the thermal properties of the two reinforcing fibers. After each wear test, scanning electron microscopy was employed to analyze the morphologies of the worn surfaces of the composite. The results of sliding wear tests show that the difference between the tribological properties of the two composites is small at room temperature. However, the hybrid PI-PTFE/Nomex fabric composite achieves better tribological properties at high temperatures compared with the hybrid Nomex-PTFE/Nomex fabric composite, which suffered wear failure at 240℃. It is proposed that the excellent thermal mechanical property and thermal stability of PI fibers is the main factor that endows the PI-PTFE/Nomex/BOZ composite with a more favorable tribological property at high temperatures. Moreover, the influence of the increasing temperature on the tribological properties of the two composites was also investigated.